High temperature storage reliability of Cu pillar flip chip interconnects - WORAPAKDEE, Kachain; SRISRUAL, Anusara (Journal of Metals, Materials and Minerals, 2026)
The Cu pillar flip chip is currently designed and used in the optic communication device that it has exhibited low reliability at high temperature. This paper aims to report the reliability of Cu pillar flip chip assembled on electronics board for a new optoelectronic product subjected to high temperature storage testing. The test was performed at 150℃ isothermal condition with the various storage times up to 2000 h. The aged samples were characterized with scanning acoustics microscopy, scanning electron microscopy, and energy dispersive X-ray spectroscopy. Two types of intermetallic compounds (IMCs) were found at beside of the Cu pillar i.e. Cu6Sn5 and Cu3Sn. The Cu3Sn layer exhibits a thinner thickness (~0.62 mm at 1000 h) and a slower growth rate (~0.27 mm/1000 h) compared to the Cu6Sn5 layer (~7.96 mm and ~2.59 mm/1000 h). Cracks were commonly found at the IMC/Cu pillar sidewall interface that initiating at the solder edge on the pillar side with the smaller solder volume, then propagating along IMC/Cu interface. At the top of Cu pillar and substrate pad, which were coated by Ni layer, only (Cu,Ni)6Sn5 was found. The Ni layer influenced both the IMC type and growth rate. All IMCs exhibited increasing thickness with storage time. These findings provide important insights into the thermal reliability of a fine pitch Cu pillar solder interconnects in advanced electronic packaging.